The potential of tasks for mathematical learning and its use in instruction – perspectives of experts from Germany and Taiwan - Lindmeier, Anke; Wang, Ting-Ying; Hsieh, Feng-Jui; Dreher, Anika (Proceedings of the 45th Annual Conference of the International Group for the Psychology of Mathematics Education, 2022)
The potential of tasks to stimulate students’ mathematical thinking and the adequate use of this potential in instruction are prominent indicators for instructional quality. Since the assessment of a task’s potential depends on the aims of instruction, it may be argued that corresponding perspectives vary between cultural contexts. However, so far, this has not been systematically investigated in cross-cultural comparisons. In this study, we investigate whether Western (German; N=17) and East Asian (Taiwanese; N=19) professors of mathematics education have different perspectives on the potential of word problems for students’ learning and the use of this potential in instruction by means of vignettes from a cross-cultural research project. We illustrate how differences reflect cultural aspects of mathematics instruction.
CRIS-Team Scopus Importer:2024-10-02